Cover, Content, and Editorial Note from Borneo J Pharm Vol. 3 Special Issue 1 June 2020 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2020)
COVID-19 is currently the most researched topic worldwide. Apart from the effects that are caused by such a massive, also because the most effective therapies to treat it has still not been found. Therefore, researchers around the world seem to compete with time to research to find ways to overcome the global pandemic. Seeing this trend, the Borneo Journal of Pharmacy (Borneo J Pharm) does not want to be left behind to participate in sharing information related to COVID-19, and Alhamdulillahirabbil 'alamin, in the middle of 2020 Borneo J Pharm published its first Special Issue with the related Research and Review theme of COVID-19. This edition contains five articles both research articles and reviews from domestic and foreign authors. The authors came from four countries consisting of Indonesia, India, Saudi Arabia, and Nigeria. The authors also come from several institutions, including Kota College of Pharmacy, Dr. A.P.J. Abdul Kalam University, Raffles University, Oxford College of Pharmacy, Shri Gopichand College of Pharmacy, Federal University of Technology Minna, University of Abuja, Benue State Polytechnic, Rahul Sankrityayan College of Pharmacy, Jamia Hamdard, Chhatrapati Shahu Ji Maharaj University, Prince Sattam bin Abdulaziz University, and Universitas Muhammadiyah Bandung